Perancangan Pemecah Gelombang di Pantai Auki Kabupaten Biak Numfor, Papua - Ixsus Alexander Sappetau; Benyamin Tanan; Erni.R. Bungin (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This study aims to prevent abrasion with a breakwater at Auki Beach. This research can be used as a consideration for the construction of breaking waves around the coast. The too big waves on Auki Beach caused the retreat of the coastline due to abrasion that threatened the lives of residents in the area. Wind data were analyzed with the Wind Rose application to determine the direction of the dominant wind. Forecasting waves based on dominant wind and fetch length refers to the Shore Protection Manual (SPM) 1984. The determination of the plan wave uses the Gumbell’s distribution method (Fisher Tipped Type I) with a return period of 2 - 100 years and for the breakwater planning refers to the equation - equations in the Beach Building Planning book. The results showed that the dominant wind direction came from the Southwest with a speed of 18 knots. The design wave height for the 50 years return period is 2.464 m. The breakwater is planned at a distance of 152.5 m from the coastline with a depth of -3.195 m. The type of breakwater used is an oblique sided breakwater with a height of 7.186 m and a thickness of 4.531 m of protection layer to prevent coastal abrasion.